2021
DOI: 10.1093/mnras/stab2134
|View full text |Cite
|
Sign up to set email alerts
|

HCN/HNC chemistry in shocks: a study of L1157-B1 with ASAI

Abstract: HCN and its isomer HNC play an important role in molecular cloud chemistry and the formation of more complex molecules. We investigate here the impact of protostellar shocks on the HCN and HNC abundances from high-sensitivity IRAM 30m observations of the prototypical shock region L1157-B1 and the envelope of the associated Class 0 protostar, as a proxy for the pre-shock gas. The isotopologues H12CN, HN12C, H13CN, HN13C, HC15N, H15NC, DCN and DNC were all detected towards both regions. Abundances and excitation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Previous studies (e.g., Goldsmith et al 1986;Herbst et al 2000;Meijerink et al 2011;Kazandjian et al 2012;Krieger et al 2020) have suggested that the HCN/HNC abundance ratio might probe mechanical heating processes in the ISM through its kinetic temperature sensitivity, with the ratio increasing at high kinetic temperatures. This behavior has been seen in observations of protostellar shocks (e.g., Lefloch et al 2021) and C-type shock models, where the HCN/HNC abundance ratio increases by a factor of ∼20. Hence, we would expect that mechanical heating by shocks in NGC 253 would produce high HCN/HNC abundance ratios (Viti 2017).…”
Section: Effect Of Cosmic Rays On the Hcn/hnc Ratiosupporting
confidence: 63%
“…Previous studies (e.g., Goldsmith et al 1986;Herbst et al 2000;Meijerink et al 2011;Kazandjian et al 2012;Krieger et al 2020) have suggested that the HCN/HNC abundance ratio might probe mechanical heating processes in the ISM through its kinetic temperature sensitivity, with the ratio increasing at high kinetic temperatures. This behavior has been seen in observations of protostellar shocks (e.g., Lefloch et al 2021) and C-type shock models, where the HCN/HNC abundance ratio increases by a factor of ∼20. Hence, we would expect that mechanical heating by shocks in NGC 253 would produce high HCN/HNC abundance ratios (Viti 2017).…”
Section: Effect Of Cosmic Rays On the Hcn/hnc Ratiosupporting
confidence: 63%
“…At high temperatures, new paths to form HCN via neutral-neutral reactions produce [HCN]/[HNC] ratios larger than 1. This simple scenario was able to explain in general terms the wealth of observational data gathered thus far: the [HCN]/[HNC] ratio is observed close to 1 in cold cores (Daniel et al 2013;Lefloch et al 2021), slightly higher than 1 (between 1 and 3) in giant molecular clouds (GMCs), and increasing to values much greater than 1 in hot cores (Jin et al 2015), Young Stellar Objects (YSOs, Jørgensen et al 2004) and luminous galaxies (ULIRGs, Baan et al 2010). However, some exceptions challenge our understanding of the chemistry of nitriles.…”
Section: Introductionmentioning
confidence: 76%
“…We also note that in García-Burillo et al ( 2014) and Viti et al (2014), large HCN(1-0)/HCO + (1-0) (as well as the ratio of higher J) was in fact associated with large scale shocks that were associated with the molecular outlfow, rather than XDR chemistry, a scenario also explored in García-Burillo et al (2010). Recent galactic studies, such as the study into the prototypical shock region L1157-B1 in Lefloch et al (2021), have shown a marked increase in HCN abundance relative to H 2 in these environments, relative to preshock gas. However, there are significant exceptions.…”
Section: Hcn/hco +mentioning
confidence: 87%